Atmospheric Transport Towards the Iberian Peninsula in the 3- to 10-Day Range - Raquel Nieto; Luis Gimeno (The Scientific World Journal)
An advanced Lagrangian atmospheric transport model (FLEXTRAP) was used to identify the possible sources of middle-lived pollutants over the Iberian Peninsula. A period of 4 years, 2000—2003, was analyzed. Transatlantic transport is the main pathway of the air reaching the Iberian Peninsula in the studied range of 3—10 days; local sources are limited to 3 days of transport. The presence of North America as a source from days 6—10 of transport identifies this region as the main potential contributor to the middle-lived pollutants over the Iberian Peninsula.